Reliability Analysis of Operation for Cableways by FTA (Fault Tree Analysis) Method - Težak, Sergej; Toš, Zdravko; Jurić, Ivo (Promet - Traffic&Transportation, 2010)
This paper examines the reliability of the operation of cableway systems in Slovenia, which has major impact on the quality of service in the mountain tourism, mainly in wintertime. Different types of cableway installations in Slovenia were captured in a sample and fault tree analysis (FTA) was made on the basis of the obtained data. The paper presents the results of the analysis. With these results it is possible to determine the probability of faults of different types of cableways, which types of faults have the greatest impact on the termination of operation, which components of cableways fail most, what is the impact of age of cableways on the occurrence of the faults. Finally, an attempt was made to find if occurrence of faults on individual cableway installation has also impact on traffic on this cableway due to reduced quality of service. KEYWORDS: cableways, aerial ropeways, chairlifts, ski-tows, quality, faults, fault tree analysis, reliability, service quality, winter tourism, mountain tourist centre